The political economy of disability in Turkey’s welfare regime - Yılmaz, Volkan. (Thesis (M.A.)-Bogazici University. Atatürk Institute for Modern Turkish History, 2010., 2010)
Turkey’s welfare regime has been undergoing a massive transformation under the auspices of the Justice and Development Party since 2002. The ratification of the Law on Disabled People in 2005 could be regarded as an important part of this transformation which introduced novel social policy programs while consolidating the preexisting ones. This study approaches disability, in the context of the capitalist welfare state, as an administrative category that entitles its holders to particular rights and privileges, especially concerning employment and social assistance policies. From this perspective, after accounting for the historical relationship between the category of disability and the welfare regime in Turkey, the study investigates the political economy of disability category with a special focus on the political process leading to the promulgation of the Law on Disabled People and its policy implications. Analyses of three empirical sources are made in this study: in-depth interviews with welfare administrators, professionals working for and representatives of disability organizations; legislations, official reports and data obtained from state institutions; and testimonies of disabled people accessed through the Engelliler.biz online forum. The study argues that the category of disability, which first came into being in the 1970s, started to gain importance in the welfare transformation of Turkey in the AKP period. The frontiers of the welfare regime in Turkey expanded by developments in social assistance and cash-for-care policies for disabled people, which connotes both liberal residualism with regard to the restricted coverage of the programs, and conservative outlook due to its ideological commitment to the myth of family solidarity. Lastly, the introduction of work conditionality to disability allowance and the restriction of eligible population due to changes made in the calculation formula of disability occurred which have been leading to the decomposition of the disability category on the basis of a person’s ability to work.
Keywords: Public welfare.; People with disabilities -- Turkey.